Cardiac and vascular effects of low-dose steroids during the early phase of septic shock: An echocardiographic study - Bagate, François; Coppens, Alexandre; Masi, Paul; de Prost, Nicolas; Carteaux, Guillaume; Razazi, Keyvan; Mekontso Dessap, Armand (Frontiers in Cardiovascular Medicine, 2022)
Background: Low-dose steroids are known to increase arterial pressure during septic shock through restoration of vasopressor response to norepinephrine. However, their effects on cardiac performance and ventriculo-arterial coupling (VAC) have never been scrutinized during human septic shock. The aim of this study was to perform a comprehensive description of the cardiovascular effects of low-dose steroids using modern echocardiographic tools (including speckle tracking imaging). Methods: This prospective study was conducted in the intensive care unit of a university hospital in France. Consecutive adult patients admitted for septic shock and requiring low-dose steroid therapy were prospectively enrolled within 24 hours of septic shock onset. We recorded hemodynamic and echocardiographic data to explore left ventricle (LV) contractility, loading conditions and VAC just before the initiation of low-dose steroids (50 mg intravenous hydrocortisone plus 50 g enteral fludrocortisone) and two to four hours after. Results: Fifty patients (65 [55-73] years; 33 men) were enrolled. Arterial pressure, heart rate, almost all LV afterload parameters, and most cardiac contractility parameters significantly improved after steroids. VAC improved with steroid therapy and less patients had uncoupled VAC (>1.36) after (24%) than before (44%) treatment. Conclusion: In this comprehensive echocardiographic study, we confirmed an improvement of LV afterload after initiation of low-dose steroids. We also observed an increase in LV contractility with improved cardiovascular efficiency (less uncoupling with decreased VAC).